Rock slope kinematics analysis by Markland method of the Bener District, Purworejo Regency, Central Java, Indonesia - Sari Bahagiarti Kusumayudha; Azwar Thamrin; Heru Sigit Purwanto (Institute of Advanced Engineering and Science, 2023)
Bener District, Purworejo Regency, Central Java, Indonesia, located in the Kulon Progo Mountains can be classified as a high-risk area. Many experts and researchers have studied landslides, but there has been little research on rock slope kinematics. In fact, when such a rock slope is unstable and poorly monitored, it has the potential to endanger the community or facilities at the adjacent site. This is why slope kinematics research is required. To complete this study, rock kinematics analysis using the Markland method was performed on six representative slopes. The assessment results show that Kaliwader slope A, Kaliwader slope B, and Argosari slope each tend to collapse with wedge failure, Kaliwader slope D and Wadas slope have the potential for wedge failure and planar slide, but Kaliwader slope C does not. Despite their steep inclination, slopes that are likely to fail are strongly related to the presence of geologic structures, particularly joints, and faults, at the sites. The findings of this study will be helpful in the development of landslide vulnerability zones in the context of disaster mitigation.